Atypical antipsychotic drugs and risk of ischaemic stroke: population based retrospective cohort study - Gill, Sudeep S (BMJ Publishing Group Ltd., 2005)
Objective To compare the incidence of admissions to hospital for stroke among older adults with dementia receiving atypical or typical antipsychotics. Design Population based retrospective cohort study. Setting Ontario, Canada. Patients 32 710 older adults (≤ 65 years) with dementia (17 845 dispensed an atypical antipsychotic and 14 865 dispensed a typical antipsychotic). Main outcome measures Admission to hospital with the most responsible diagnosis (single most important condition responsible for the patient's admission) of ischaemic stroke. Observation of patients until they were either admitted to hospital with ischaemic stroke, stopped taking antipsychotics, died, or the study ended. Results After adjustment for potential confounders, participants receiving atypical antipsychotics showed no significant increase in risk of ischaemic stroke compared with those receiving typical antipsychotics (adjusted hazard ratio 1.01, 95% confidence interval 0.81 to 1.26). This finding was consistent in a series of subgroup analyses, including ones of individual atypical antipsychotic drugs (risperidone, olanzapine, and quetiapine) and selected subpopulations of the main cohorts. Conclusion Older adults with dementia who take atypical antipsychotics have a similar risk of ischaemic stroke to those taking typical antipsychotics.